A Study on Research and Development Cost Stickiness: Evidence from Technology Companies - 윤소라 (경영학연구, 2021)
The purpose of this study is to examine whether R&D cost stickiness exists and the sticky behavior of R&D expense is pronounced in technology industries. The study entails testing for sticky cost behavior by comparing sales revenue in periods when revenue increases with variations in R&D expenses with revenue in periods when revenue decreases with these variations. The analysis of 109,757 firm-year observations over 41 countries from 2010 to 2019 reveals an absence of R&D expense stickiness across the entire sample; the results show that companies more aggressively reduce their R&D expenses when their sales decline, although there is statistically significant R&D expense stickiness for technology companies; this finding implies that tech managers do not reduce R&D expenditures even with declining revenue. These managers recognize R&D as an essential element for continuous innovation and survival. The findings of this study expand the empirical research on R&D expenditures and cost behavior; they can be used as a practical basis for R&D budgeting and to emphasize the need for continuous investment in R&D activities.
Keywords: cost stickiness; technology industries; R&D intensity